The effect of the Vaalkop replacement pegmatoid on the sulphide mineralogy at Western Platinum mine in the Mooinooi district - Merkle, R.K.W. (Roland Karl Willi), 1954- (University of Pretoria, 2022)
Dissertation (MSc)--University of Pretoria, 1995.